The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s10530-021-02600-w
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Ceratium furcoides in subtropical lakes in Uruguay: Environmental drivers and fish kill record during its bloom

Abstract: The invasive freshwater dino agellate Ceratium furcoides is extending its distribution in South America with increasing environmental impacts associated with its blooms. We here report two events related to C. furcoides distribution expansion in Uruguay: 1) the rst appearance and main environmental drivers (physico-chemical variables, extreme wind events and zooplankton composition) of the bloom of C. furcoides in 2012 in a subtropical eutrophic shallow lake (Lake Blanca, Uruguay), and 2) the sh kill event of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
(65 reference statements)
3
4
0
3
Order By: Relevance
“…Other studies have shown the success of the invasion of C. furcoides in aquatic bodies in the subtropical region(Cavalcante et al, 2013(Cavalcante et al, , 2016Silva et al, 2018;Silva et al, 2019).Although high temperatures may bene t Ceratium, this is not a determining factor for its expansion, as the dino agellate maintains intermediate densities in later years (2016 onwards). This coincides with other studies, such as in Lake Blanca, Uruguay(Pacheco et al, 2021), where high temperatures were important during the initial stages of a bloom but not necessary to maintain it. C. furcoides has complex distribution and expansion patterns, usually colonizing freshwaters from basins that are geographically close(Moreira et al, 2015;Silva et al, 2018;Pacheco et al, 2021).Common phytoplankton dispersants such as wind, animals, and humans could play a part on the expansion of the dino agellate as they can be a very effective disperse…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Other studies have shown the success of the invasion of C. furcoides in aquatic bodies in the subtropical region(Cavalcante et al, 2013(Cavalcante et al, , 2016Silva et al, 2018;Silva et al, 2019).Although high temperatures may bene t Ceratium, this is not a determining factor for its expansion, as the dino agellate maintains intermediate densities in later years (2016 onwards). This coincides with other studies, such as in Lake Blanca, Uruguay(Pacheco et al, 2021), where high temperatures were important during the initial stages of a bloom but not necessary to maintain it. C. furcoides has complex distribution and expansion patterns, usually colonizing freshwaters from basins that are geographically close(Moreira et al, 2015;Silva et al, 2018;Pacheco et al, 2021).Common phytoplankton dispersants such as wind, animals, and humans could play a part on the expansion of the dino agellate as they can be a very effective disperse…”
supporting
confidence: 91%
“…This coincides with other studies, such as in Lake Blanca, Uruguay(Pacheco et al, 2021), where high temperatures were important during the initial stages of a bloom but not necessary to maintain it. C. furcoides has complex distribution and expansion patterns, usually colonizing freshwaters from basins that are geographically close(Moreira et al, 2015;Silva et al, 2018;Pacheco et al, 2021).Common phytoplankton dispersants such as wind, animals, and humans could play a part on the expansion of the dino agellate as they can be a very effective disperse…”
supporting
confidence: 91%
See 1 more Smart Citation
“…and a permanent clear water regime. The dominant phytoplankton taxonomic groups, in this lake, have changed through the years from cyanobacteria to chlorophytes (Kruk et al, 2006;Pacheco et al, 2010), with one event of a Ceratium furcoides (Levander) bloom in 2012 (Pacheco et al, 2021). The community of consumers in the clear-vegetated lake is diverse; the zooplankton community is dominated by small-bodied cladocerans and copepods, with occasional occurrence of Daphnia spp.…”
Section: Methodsmentioning
confidence: 99%
“…The community of consumers in the clear-vegetated lake is diverse; the zooplankton community is dominated by small-bodied cladocerans and copepods, with occasional occurrence of Daphnia spp. and other larger-bodied species, the diverse fish community dominated by small-bodied species with a high biomass (Pacheco et al, 2021). Lake Capilla (location: 34°49 0 18.5 00 S-54°37 0 48.7 00 W, area: 1 ha), hereinafter referred to as 'phytoplankton-turbid', is a small, young (less than 15 years) artificially constructed lake that is in a turbid state due to high phytoplankton biomass.…”
Section: Methodsmentioning
confidence: 99%